2013
DOI: 10.1007/s00213-013-3115-8
|View full text |Cite
|
Sign up to set email alerts
|

Central nervous system effects of prenatal selective serotonin reuptake inhibitors: sensing the signal through the noise

Abstract: Rationale Women are increasingly prescribed selective serotonin reuptake inhibitors (SSRIs) during pregnancy, with potential implications for neurodevelopment. Whether prenatal SSRI exposure has an effect on neurodevelopment and behavior in the offspring is an important area of investigation. Objectives The aim of this paper was to review the existing preclinical and clinical literature of prenatal SSRI exposure on serotonin-related behaviors and markers in the offspring. The goal is to determine if there is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 136 publications
1
9
0
Order By: Relevance
“…The similar effect size of this group to that of SSRI exposure any time during pregnancy group with a largely overlapping confidence interval strengthens our previous suggestion that the maternal psychiatric disorder may be a strong confounder in studies assessing the connection between maternal SSRI use and ASD risk in children . Although sought by an increasing number of studies and considered as biologically plausible , the suggested association of SSRI exposure during pregnancy and risk of ASD in children still remains to be adequately substantiated.…”
Section: Discussionsupporting
confidence: 79%
“…The similar effect size of this group to that of SSRI exposure any time during pregnancy group with a largely overlapping confidence interval strengthens our previous suggestion that the maternal psychiatric disorder may be a strong confounder in studies assessing the connection between maternal SSRI use and ASD risk in children . Although sought by an increasing number of studies and considered as biologically plausible , the suggested association of SSRI exposure during pregnancy and risk of ASD in children still remains to be adequately substantiated.…”
Section: Discussionsupporting
confidence: 79%
“…Psychosocial services that promote the mother-child relationship also may be needed to help optimize the postnatal environment and thereby positively affect child development (Forman et al, 2007). Gur et al (2013) have reasoned that since serotonin (5-HT) modulates neuroplasticity, the impact of SRI exposure on fetal brain development likely is significant, but may evolve over time and be context dependent. Similarly, Brummelte, Mc Glanaghy, Bonnin, and Oberlander, (2016) suggest that prenatal exposures that change 5-HT levels may act as plasticity rather than risk factor per se.…”
Section: Discussionmentioning
confidence: 99%
“…Further, other studies using animal models show that preclinical findings in rodents exposed to SSRIs during development point to an increase in depression and anxiety, exhibiting alteration in social behaviors in the offspring. The data show adverse effects of maternal mental illness on pregnancy outcomes and infant neurodevelopment but are not robust enough to discourage the use of SSRIs during human pregnancy [ 66 ]. In a study by Gur et al [ 66 ], it was shown that the manipulation of serotonin during early development in both in vitro and in vivo models disturbs characteristic chemoarchitectural and electrophysiological brain features.…”
Section: Discussionmentioning
confidence: 99%
“…The data show adverse effects of maternal mental illness on pregnancy outcomes and infant neurodevelopment but are not robust enough to discourage the use of SSRIs during human pregnancy [ 66 ]. In a study by Gur et al [ 66 ], it was shown that the manipulation of serotonin during early development in both in vitro and in vivo models disturbs characteristic chemoarchitectural and electrophysiological brain features. This includes changes in raphe and callosal connections, sensory processing, myelin sheath formation, neophobia, and disrupted juvenile play behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation